Is the MAPK ERK5 the nexus from FAO to NK cell-mediated metastasis immune surveillance? - Villalba, Martin; Gitenay, Delphine; Zemiti, Sara; Rossi, Jean-François; Campos-Mora, Mauricio (Frontiers in Immunology, 2025)
Mammalian cells adapt to their environment by reshaping their metabolism. Increased fatty acid oxidation (FAO) enables metastatic cells to enhance their motility and colonize new niches, where the fatty acid transporter CD36 functions as both marker and driver of this process. The MAPK ERK5 regulates CD36 expression, FAO, and the epithelial-mesenchymal transition (EMT), a critical initial step in metastasis. Contrary to popular belief, metastasis is a highly inefficient process, in part due to natural killer (NK) cell immune surveillance. This cytotoxic lymphocyte lineage detects inhibitory and activating ligands on target cells to determine their fate. During EMT, the expression of specific ligands on metastatic cells triggers their recognition by NK cells. Interestingly, several of these ligands are regulated by ERK5. We hypothesize that ERK5 may serve as a central link between FAO, metastasis, and immune surveillance. Here, we review current knowledge and available evidence regarding ERK5 expression in tumor cells and its role in cancer cell migration and metastasis and speculate in the potential role of ERK5 in immune recognition and the clearance of metastasis by NK cells.